Feeding habits of the ichthyofauna in a protected area in the State of São Paulo, southeastern Brazil - Gomiero, Leandro Muller [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (Instituto Virtual da Biodiversidade, 2008)
Foram analisadas duas bacias em uma área com forte ação antrópica no interior do Estado de São Paulo, enfocando as relações tróficas das comunidades de peixes. Foram analisados 211 estômagos de 14 espécies. As dietas foram variadas sendo constatadas piscívoria, bentofagia, insetívoria, herbívoria e iliófagia. Os itens alimentares foram descritos para cada espécie analisada e verificou-se grande quantidade de insetos. Os itens alimentares alóctones e autóctones foram importantes em maior ou menor grau para as espécies da área. O índice de repleção estomacal elevou-se na primavera e no verão em ambas bacias, sendo que as áreas abordadas foram usadas para a reprodução e para a alimentação coletiva das espécies analisadas.

The trophic relationships of a fish community were studied in two basins subjected to a strong human pressure in the interior of the State of São Paulo, southeastern Brazil. A total of 211 stomachs of 14 species were analyzed. Diets varied greatly, with the occurrence of piscivory, benthophagy, insectivory, herbivory, and illiophagy. Food items were described for each species and a great amount of insects was registered. Allochthonous and autochthonous food items showed different importance degrees according to the species analyzed. Stomach fullness was high in spring and summer in both basins; these areas were used as reproduction and foraging sites for the studied species.
Hábitos alimentares da ictiofauna em uma área de proteção ambiental no estado de São Paulo, sudeste do Brasil
Keywords: alimentação; relação trófica; ictiofauna; APA de São Pedro e Analândia; feeding habits; trophic relation; ichthyofauna; protected area of São Pedro and Analândia